The Correlation of Parenting and Socioeconomic Status Towards English Learning Readiness of Children - Andi Ummul Khair (Universitas Cokroaminoto Palopo, 2014)
This research is about the correlation of Parenting and Socioeconomic Status (SES) towards English Learning Readiness (ELR) of children. This study was aimed to find out the correlation of parenting quality and socioeconomic status towards English learning readiness of children. This research applied quantitative research, the case conducts in correlational research which describes an existing condition. The population of this research was students from all elementary school in Kecamatan Tamalate Makassar where English is tought at second grade. The representation of the population in this research is the 2nd year students of six elementary schools in Kecamatan Tamalate academic year of 2012/2013 who have collected the two questionnaires which is distributed to them and filled out by their parents. Total number of the sample is 105 students chosen from the questionnaires which is collected and has filled properly by parents. The data were obtained by using two kinds of instruments, those are questionnaires of parenting and socioeconomic status which have tested the validity in a number of students and data of the ELR of children got from student’s English achievement in school. Those data were analyzed by using path analysis of Amos 20.0. The researcher concludes that (1) the correlation of parenting with ELR indicates the higher quality of parenting they have the higher children gain ELR, on the contrary the less quality of parenting they have the less children gain ELR, (2) SES has almost none indication to have correlation with ELR, (3) The higher SES the better parenting do and the lower SES the worst parenting do.